One Week in January: A Register of Men from Late Antique Egypt - Cromwell, Jennifer.
The University of Michigan papyrus P.Mich. inv. 1545 is a register of men, written in Coptic. Various pieces of information are provided for each man, including their patronymic, their place of residence, their occupation, or the name of the person they served. Occupations include dealers of various commodities, gardeners, and herders. Where toponyms can be identified, they are from the Hermopolite nome. It is argued that this register records the male visitors to the monastery of Apa Apollo at Bawit, near Hermopolis, during a period of one week in Tobe (January) in the seventh/ eighth century CE.